Analisis Kebijakan Pengelolaan Pajak Daerah Dalam Meningkatkan PAD di Kota Pematang Siantar - Pawer Panjaitan; Darwin Damanik; Octa Saragih; Hartati Sitio; Tia Saragih; Sintong Simanjuntak; Grace Naibaho; Savirgi, Savirgi (CV. Ulil Albab Corp, 2025)
The aim of the research conducted by researchers is to determine the extent to which local original income has increased through regional tax management mechanisms. The Regional Revenue Agency is the Department responsible for managing local revenue. For this reason, researchers are interested in conducting research related to